Biologi Parasitoid Koinobiont Opius sp. (Hymenoptera: Braconidae) Pada larva Lalat Pengorok Daun Liriomyza huidobrensis (Diptera: Agromyzidae) - Hari PURNOMO; Sigit PRASTOWO; Moh. Wildan DJADMIKO; Shohab MABDUH (Jurnal Pengendalian Hayati, 2008)
Opius sp. is koinobiont endoparasitoid of L. huidobrensis larvae. Opius sp. has shortlife cycle, high fecundity and able to parasite at different larvae stages. The research objective was todetermine effect of larvae stages of LMF on parasitsm, fitness, development time and longevity ofOpius sp. The research was conducted at Laboratory of Biological Control and Glass house of Pestand Plant Diseases Departement, Agriculture Faculty, Jember University from from April until July2007. The insect were collected from Ngadisari, subdistrict of Sukapura, Probolinggo. The experimentwas done on two methods, choice and non choice test. Percentage of parasitization, the sting time,development time, longevity, sex ratio, body lenght, hind and hind tibia of adult female and male ofparasitoid Opius sp were examined. The result showed that the sting time of Opius sp. was influencedby larvae. The lates stages of LMF has the higher sting time compare early stages, 44,28 s on firstinstar, 54,9 s on second instar, and 80,68 third instar respectly. Parasitization of parasitoid Opius sp.was not influenced by larvae stage of L. huidobrensis. The percentage of parasitization on choice testwas 28,49% on first instar, 17,43% on second instar and 14,95% third instar. On the other hand, onnon chice test was 48,21% on first instar, 54,52% on second instar and 54,00% on third instar. Sexratio, adult fitness, body length, hind and hind tibia length, development time, longevity wereinfluenced by larvae stages.